Pengaruh Komitemen Mengajar Terhadap Pencapaian Kinerja Optimum Guru Di SMA Yappenda - Itsna Fakhria; Muharomah Ayu Safa’atun; Rohmatul Amaliyah Al-Fauziah (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
Education is one of the important factors in advancing the civilization of a country. Through productive teacher performance, the education process can run well. The results of the learning process carried out by teachers and students are expected to produce graduates who are able to compete and quality. Therefore, teacher commitment is needed to achieve the expected results. This study aims to determine the effect of teacher commitment on teacher performance in implementing learning, especially teachers at YAPPENDA High School, North Jakarta. This research uses a qualitative method, by distributing questionnaires to YAPPENDA High School students, interviews with YAPPENDA High School teachers, and from reference sources related to this research. The results showed that: (1) teachers have good commitment, as well as good teacher performance; (2) there is a strong influence between teacher commitment and teacher performance; (3) the positive effect of teacher commitment on teacher performance is significant.